Handel emisjami w Unii Europejskiej jako instrument ograniczania wpływu lotnictwa na zmiany klimatyczne - Borys, Grażyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The objective of the hereby article is to present the influence of aviation on climatic changes as well as activities taken up in the European Union to limit such influence. The EU system of aviation sector entitlement (which is being prepared for implementation starting from 2008) to perform such emissions trading is analyzed in particular. It will probably be a separate emissions trading system from the one which has already been functioning since 2005 and covering other than aviation sectors of economy. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (7); 2007; nr 1185, s. 22-29